Factors Associated with Fecal Incontinence in Women of Childbearing Age with Crohn's Disease. Issue 5 (6th April 2017) - Brochard, Charlène; Siproudhis, Laurent; Levêque, Jean; Grouin, Amélie; Mallet, Anne-Laure; Bretagne, Jean-François; Ropert, Alain; Bouguen, Guillaume
Abstract : Background: Fecal incontinence is common in women with Crohn's disease, but little is known about the impact of childbirth, perianal Crohn's disease, and past surgical history on fecal incontinence. Methods: Self-administered questionnaires were mailed to consecutive women referred to a tertiary gastroenterology centre with a focus on fecal incontinence and childbirth. These data were cross-referenced with a prospective database of the same patients' own Crohn's disease histories. Fecal incontinence was defined as a Cleveland Clinic Incontinence Score ≥5. Factors associated with fecal incontinence were analyzed. Results: A total of 173 patients were assessed, including 113 parous women. The prevalence of fecal incontinence was 37.5% (95% CI, 30.7–45.0). The disease duration, a history of anal surgery for fistula, the number of childbirths per woman and Crohn's activity were all independently associated with fecal incontinence in a multivariate analysis model. Specifically, among the group of parous women, fecal incontinence was associated with prior abdominal surgery, prior anal surgery, and Crohn's activity. The mode of delivery was not statistically associated with fecal incontinence. Conclusions: Fecal incontinence is a significant complaint in at least one-third of women of childbearing age with Crohn's disease. Patients'disease and treatment histories seem to have a comparable effect to their childbirth history concerning the presence of fecal incontinence. Both physicians and surgeons who are involved in the management of Crohn's disease need to keep this in mind.